Induction of genetic variant of Artemisia annua L. was conducted through the application of gamma ray irradiation in 2007-2008. The aim was to obtain a plant with high artemisine content > 0.5% and late flowering period of about > 7 month after planting. Tweleve selected genotypes were subsequently examined to gain genetic stability on altitude of 1500, 950, and 540 m asl. The results showed that the plants had shorter flowering age in Cicurug (540 m asl) than that of in Pacet (950 m asl) and G - ENDANG GATI LESTARI ENDANG GATI LESTARI ENDANG GATI LESTARI; MUHAMAD SYUKUR; RAGAPADMI PURNAMANINGSIH; ROSSA YUNITA; ROHIM FIRDAUS (Bogor Agricultural University, Indonesia, 2011)
Induction of genetic variant of Artemisia annua L. was conducted through the application of gamma ray irradiation in 2007-2008. The aim was to obtain a plant with high artemisine content > 0.5% and late flowering period of about > 7 month after planting. Tweleve selected genotypes were subsequently examined to gain genetic stability on altitude of 1500, 950, and 540 m asl. The results showed that the plants had shorter flowering age in Cicurug (540 m asl) than that of in Pacet (950 m asl) and Gunung Putri (1540 m asl). Genotype 8 had the latest age of flowering in the three locations than the other genotypes, however, the growth and biomass were the lowest. Vegetative growth of Artemisia in Pacet and Gunung Putri was better than those in Cicurug. Genotype of 15 in Cicurug and 5A genotype in Gunung Putri and Pacet had higher wet and dry weight than that of two other associates. Based on plant biomass, 5 genotypes from Gunung Putri and Pacet i.e. 1D, 3, 5A, 14, and 15 genotypes were selected, as well as 5 genotypes i.e. 1D, 3, 4, 5A, and 15 genotypes from Cicurug. Analisys on artemisin content successfully obtained 5 selected somaclone lines i.e. 1B, 2, 4, 14, and 3 somaclones.